Multimodal imaging features of intraocular foreign bodies. (17th November 2019) - Rong, Andrew J.; Fan, Kenneth C.; Golshani, Behrad; Bobinski, Matthew; McGahan, John P.; Eliott, Dean; Morse, Lawrence S.; Modjtahedi, Bobeck S.
ABSTRACT: Objective : To determine the imaging approach for evaluating intraocular foreign bodies (IOFBs) by comparing the ability of different modalities [plain film x-ray, computed tomography (CT), magnetic resonsance imaging (MRI), convetional ultrasound, and ultrasound biomicroscopy] to detect and characterize IOFBs. Methods & Design : Systematic review of the literature. Results : CT is the most practical first step for evaluating patients with suspected IOFBs because it can detect a wide range of IOFB types at small limitis of detection. MRI and ultrasound are best reserved as adjunctive tests in most cases although these tests may provide important insights especially with wood, plastic, and glass IOFBs. Imaging characteristics of metal, wood, glass, plastic, stone, concrete, and graphite IOFBs are reviewed. Conclusion : Understanding the limits of detection for each IOFB type and imaging modality as well as the characteristic features of different IOFBs is of paramount importance to optimizing the management of ocular trauma patients.